2023
DOI: 10.1021/acs.est.2c07322
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Inventory of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans and Other Byproducts along Manufacturing Processes of Chlorobenzene and Chloroethylene

Abstract: Chlorinated organic chemicals are produced and used extensively worldwide, and their risks to the biology and environment are of increasing concern. However, chlorinated byproducts [e.g., polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs)] formed during the commercial manufacturing processes and present in organochlorine products are rarely reported. The knowledge on the occurrences and fate of unintentional persistent organic chemicals in the manufacturing of organochlorine chemical is necessary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The nontarget analysis data indicated that benzene-ring-containing chemicals such as phenols and benzaldehyde were abundant in the samples. Such chemicals could act as precursors for the formation of PAHs, PCBs, PCNs, and Cl/Br-PAHs, which are toxic . It has been proposed that phenyl addition cyclization, in which phenyl radicals react to give PAHs, could occur and that naphthalene readily forms through such reactions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nontarget analysis data indicated that benzene-ring-containing chemicals such as phenols and benzaldehyde were abundant in the samples. Such chemicals could act as precursors for the formation of PAHs, PCBs, PCNs, and Cl/Br-PAHs, which are toxic . It has been proposed that phenyl addition cyclization, in which phenyl radicals react to give PAHs, could occur and that naphthalene readily forms through such reactions .…”
Section: Resultsmentioning
confidence: 99%
“…Such chemicals could act as precursors for the formation of PAHs, PCBs, PCNs, and Cl/ Br-PAHs, which are toxic. 68 It has been proposed that phenyl addition cyclization, in which phenyl radicals react to give PAHs, could occur and that naphthalene readily forms through such reactions. 69 These results and the nontarget screening results indicated that benzene homologues and derivates made larger contributions to the chemicals in bovine milk than to the chemicals in infant formula and milk powder and that processing caused the number of polycyclic aromatic hydrocarbons to increase.…”
Section: Effects Of Different Packaging Materials On Pcn Concentratio...mentioning
confidence: 99%
“…Similar to the BAF model in biofilm, log K ow also has the highest standardized coefficient (Table 2), while dipole moment (μ), which is commonly employed to describe the polarity of a molecule, 64 made a negative contribution to BMF. For those chemicals with increased μ, they are more readily dissolved in polar solvents like water, which prevents them from accumulating in organic phase.…”
Section: Standards and Reagentsmentioning
confidence: 99%
“…Chlorinated volatile organic compounds (CVOCs), including dichloromethane, dichloroethane, trichloroethylene, and chlorobenzene (CB) etc., are a fairly intractable class of air pollutants. , Compared with other nonhalogenated VOCs, CVOCs have high toxicity, chemical stability, and strong dioxin relevance, which pose a serious threat to public safety and human health. In addition, CVOCs emitted from coal-fired power plants, waste-to-energy plants, and other industrial sectors often coexist with other impurity components (typically water vapor), increasing the complexity of the treatment process. , Catalytic oxidation is widely recognized as the most promising technology for efficient purification of VOCs . As for CVOCs oxidation catalysts, in addition to catalytic activity, chlorine resistance and polychlorinated byproduct selectivity are also critical evaluation indicators. These two properties determine the stability and environmental risk of the catalyst application.…”
Section: Introductionmentioning
confidence: 99%